Assessment of the possibility of using the method of sludge-lignin dehydration of the Baikal Pulp and Paper Mill by the freeze-thaw method - Stom, DI; Zhdanova, GO; Potekhin, SA; Balayan, AE; Saksonov Saksonov, MN; Butyrin, MV; Kondratiev, VV; Ivanov, NA; Spirin, V; Kizeev, DA (International Journal of Engineering and Technology, 2018)
An estimation of the possibility of dehydration of sludge-lignin of the Baikal Pulp and Paper Mill by the freeze-thaw method was carried out. Change of sludge-lignin structure, physicochemical properties and chemical composition after freeze-thaw are shown. Toxicity and chemical composition of the water solution separated from the sludge-lignin during its freeze-thaw is estimated. An increase in the rate of germination of seeds of the cress in the soil with the addition of the frozen-out sludge-lignin in the ratio "sludge-lignin-soil" 1:3-1:4 is shown. Possibility of application and recommendations for the use of freezed out sludge-lignin as an organic fertilizer is considered. Principal possibility of the worm transformation of sludge-lignin, previously dehydrated by the freeze-thaw method, by red Californian worms Eisenia foetida Andrei Bouche (1972) is shown. The issue of prospects for processing this waste in a fertile bio-soil is discussed. The latter can later be used for recultivation of the territory of the sludge accumulator plots of the Baikal Pulp and Paper Mill.Â Â